Ferroptosis involves in intestinal epithelial cell death in ulcerative colitis - Xu, Minyi; Tao, Jin; Yang, Yidong; Tan, Siwei; Liu, Huiling; Jiang, Jie; Zheng, Fengping; Wu, Bin (Cell death & disease, 2020)
Ferroptosis has recently emerged as an iron-dependent form of nonapoptotic cell death, which is also a regulated necrosis process and a response to tumor suppression. However, whether ferroptosis is involved in ulcerative colitis (UC) is unknown. The aims of this study were to investigate whether the ferroptosis is involved in UC, particularly intestinal epithelial cell (IEC) death, and to analyze the effect of the nuclear factor kappa Bp65 subunit (NF-κBp65) on ferroptosis. The gene expression of ferroptosis-related proteins was assessed in intestinal mucosal samples from human UC. The experimental model of UC was induced with dextran sulfate sodium (DSS). Ferroptosis of IECs was evaluated, the effect of NF-κBp65 on ferroptosis was analyzed by using IEC-specific NF-κBp65 -deleted mice (p65 IEC-KO ), and the ferroptosis signaling pathway was investigated in vitro and in vivo. The results showed that ferroptosis was significantly induced in the IECs from UC patients and mice with colitis, and the ferroptosis was mediated by endoplasmic reticulum (ER) stress signaling. The specific deletion of IEC NF-κBp65 clearly upregulated ferroptosis and exacerbated colitis, and the result showed that phosphorylated-NF-κBp65 significantly inhibited ER stress signaling by directly binding eukaryotic initiation factor 2α. These data indicate that ferroptosis contributes to UC via ER stress-mediated IEC cell death, and that NF-κBp65 phosphorylation suppresses ER stress-mediated IEC ferroptosis to alleviate UC. The results suggest that ferroptosis involves in IEC death in UC, NF-κBp65 play a critical role in the ferroptotic inhibition, and ferroptosis is a potential therapeutic target for UC.